2018
DOI: 10.1002/hep.30095
|View full text |Cite
|
Sign up to set email alerts
|

The Immunobiology of Receptor Activator for Nuclear Factor Kappa B Ligand and Myeloid‐Derived Suppressor Cell Activation in Immunoglobulin G4–Related Sclerosing Cholangitis

Abstract: The primary function of myeloid-derived suppressor cells (MDSCs) is reflected in their immune modulatory role in several immune-mediated diseases. In immunoglobulin G4 (IgG4)-related disease (IgG4-RD), it has been hypothesized that there are selective regulatory defects that lead to a T helper 2 (Th2) bias immune response. Herein we have taken advantage of a large cohort of patients with IgG4-related sclerosing cholangitis (IgG4-SC), the most common extrapancreatic involvement of IgG4-RD, as well as controls c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Our previous studies have indicated that targeting T-cells is key to alleviating inflammatory diseases (24,44,58). Other studies have also suggested that MDSCs suppress inflammation by inhibiting the over-activation of T-cells (61,62). Consistent with the published literature, we also demonstrated that adoptive transfer with BQ123-induced PMN-MDSCs can alleviate acute inflammation in the presence of T-cells.…”
Section: Bq123-induced Pmn-mdscs Controlled Acute Inflammation In T-csupporting
confidence: 90%
“…Our previous studies have indicated that targeting T-cells is key to alleviating inflammatory diseases (24,44,58). Other studies have also suggested that MDSCs suppress inflammation by inhibiting the over-activation of T-cells (61,62). Consistent with the published literature, we also demonstrated that adoptive transfer with BQ123-induced PMN-MDSCs can alleviate acute inflammation in the presence of T-cells.…”
Section: Bq123-induced Pmn-mdscs Controlled Acute Inflammation In T-csupporting
confidence: 90%
“…Confocal laser scanning microscopy was used for co‐staining detection of two primary antibodies, as previously described. ( 29 ) After antigen retrieval, liver samples were incubated with two primary antibodies together overnight at 4°C. Primary antibodies included CD103 (ab238010), CD8 (ab93278, ab17147), CD69 (ab233396), granzyme B (ab255598), IFN‐γ (ab231036), CCR7 (ab227768), CD62L (ab264045), E‐cadherin (ab40772), and CK8‐18 (ab17139) (all from Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…Confocal laser scanning microscopy was used for the detection of costaining markers, as described. ( 24 ) Briefly, after antigen retrieval, liver samples were incubated with donkey serum for 30 minutes before being incubated with primary antibodies MTH1 (ab200832; Abcam), CD3 (60181‐1‐Ig; Proteintech), CD4 (ab67001; Abcam), and CD8 (ab17147; Abcam) at 4°C overnight. After three washes with PBS, the slides were incubated with fluorochrome‐conjugated secondary antibodies (1:200; Invitrogen) at room temperature for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%